(untitled) (Journal of the College of Basic Education, 2025)
The present study consists of four chapters. The first chapter addresses the research problem, which revolves around the following questions: What is the effect of using theatrical activities in developing creative thinking among intermediate school students? What are the prevailing creative thinking skills among intermediate school students? What is the impact of theater on developing students’ intellectual skills? The importance of this study lies in exploring the effect of employing school theater in developing students’ creative thinking skills, with the aim of identifying the effectiveness of this method in enhancing their cognitive and creative abilities. It also contributes to enriching the educational field with practical strategies that foster creativity and support students’ holistic development. The research aimed to identify the prevailing creative thinking skills among intermediate school students and to examine the effect of theatrical activities on the development of those skills. This chapter also included the research limits, hypotheses, and definitions of terms. Chapter Two comprised the theoretical framework and previous studies, with discussions. The theoretical framework contained two sections: the first covered theater, its concept, educational and creative significance, objectives, and the teacher’s role in activating theater within the classroom. The second section addressed the concept of the mind, creative thinking, its skills, its development across educational stages, and the relationship between theater and creative thinking skills. Chapter Three focused on the research procedures, which included the research population consisting of 276 first-grade intermediate students, and the sample of 68 students divided equally into two groups: experimental (34) and control (34). Purposeful theatrical activities were applied to the experimental group. Chapter Four presented the results, which revealed statistically significant differences in favor of the experimental group in the post-test of creative thinking skills. Furthermore, the experimental group showed improvement between the pre-test and post-test applications.The study recommended giving greater attention to theater in the teaching and learning process across all educational stages, in ways that suit students’ readiness and abilities. It also emphasized the importance of providing school theater halls and equipping them with the necessary resources, as well as promoting a culture of interactive teaching among students